EFISIENSI PRODUKSI PETANI KARET DI KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - elinur elinur; Heriyanto Heriyanto; Joko Saputra (Indonesian Journal of Agricultural Economics, 2018)
Smallholder rubber plantations in Riau in general have not reached high level of productivity. This study aimed to analyze the level of production efficiency from the technical, allocative and economic efficiency aspects of each sample farmer and the target to achieve technical, allocative and economic efficiency. This research was conducted using a survey method in Tapung Hulu District, Kampar Regency. The data used in this study consisted of primary data obtained using the interview method. Samples were taken by simple random sampling method consisted of 45 rubber farmers. Data analysis applied the Data Enveloment Analysis (DEA) method. The results of the study showed that most farmers have rubber inefficiencies that are technically, allocatively and economically. Thus the farmers must implement optimal input usage combined with cost minimization to achieve maximum profit in order to achieve production efficiency.